The Importance of \"Super Sensible Substrate\" in Kant\'s System of Philosophy - R Mahoozi (Metaphysics, 2013)
In Kant's transcendental philosophy, "sensible" is an object composed of multiple sense intuitions and a priori constitutive of mind. In this philosophy, sensible nature is empirical and mechanical that becomes universal and necessary under determinate concepts and principles of Understanding. But, there is another space not determined by concepts and principles of Understanding. This space is "super sensible". This super sensible is the space of noumenal objects and is very important in Kant's system of philosophy. This sphere is important for explaining the principle of uniformity of nature as a supporter to induction, some ethical items and religion theory, organisms and culture. But how can we get at this realm? And is this realm compatible with the realm of empirical knowledge? In this paper we want to explain these matters.